Employment and Work Ability of Persons With Brain Tumors: A Systematic Review - Silvaggi, Fabiola; Leonardi, Matilde; Raggi, Alberto; Eigenmann, Michela; Mariniello, Arianna; Silvani, Antonio; Lamperti, Elena; Schiavolin, Silvia (Frontiers in Human Neuroscience, 2020)
Brain tumors (BT) are between the eight most common cancers among persons aged 40 years, with an average survival time of 10 years for patients affected by non-malignant brain tumor. Some patients continue to work, reporting difficulties in work-related activities, or even job loss. The purpose of the present study was to review the existing information about the ability people with BT to return to work and to identify factors associated with job loss. We performed a systematic review on SCOPUS and EMBASE for peer-reviewed papers that reported studies assessing work ability in patients with BT that were published in the period from January 2010 to January 2020. Out of 800 identified records, 7 articles were selected for analysis, in which 1,507 participants with BT were enrolled overall. Three main themes emerged: the impact of neuropsychological functioning on work productivity, the change of employment status for long-term survivors and issues related to return to work processes. Based on the results of selected studies, it can be concluded that the impact of BT on workforce participation is determined by depressive symptoms and cognitive deficits, as well as by high short-term mortality but also on environmental barriers. Vocational Rehabilitation programs should be implemented to help patients wishing to return to or maintain their current work, as much as possible.